Evaluation of The Village Empowerment Policy / Kelurahan Mandiri Gotong Royong By The Community and Family Empowerment Agency Planning to Make Village Independence in Subang District - Sumarna Sumarna; Soleh Suryadi; R. Taqwaty Firdausijah (Pasundan Social Science Development, 2021)
Based on the observation results, the Village / Kelurahan Empowerment Policy for Independent Mutual Cooperation by the Community Empowerment and Family Planning Agency in Realizing Village Independence in Subang Regency has not been implemented optimally. Of course, there has not been a significant change in terms of services and development, either directly or indirectly, in increasing the degree of community welfare, so that overall it is still necessary to handle it optimally. The research method used is descriptive analysis, while the type of approach in this research is qualitative. The type of qualitative approach used is the institutional model case study evaluation. Qualitative research is a research procedure that produces descriptive data in written or spoken words from people and observable behavior. The qualitative method was chosen considering that this method is expected to obtain accurate data and examine research problems in depth so that the expected results can be obtained. Evaluation of the empowerment policies of villages / sub-districts independent of cooperation by the Community Empowerment and Family Planning Agency. Some factors evaluate the empowerment policy of the Village / Kelurahan Mandiri Gotong Royong by the Community Empowerment and Family Planning Agency. In realizing the independence of the Village in Subang Regency, it has not been implemented effectively. The Community Empowerment and Family Planning Agency of Subang Regency towards the people of Subang Regency has not been running effectively, because there is no continuous guidance from the Regency Government to villages in Subang Regency, so that village development continues without management, the assessment stages of Village / Village Program Policy The old Mandiri Gotong Royong has made the Village saturated. Based on the results of the SWOT analysis, the priority problems that must be addressed are selected so that the results are maximized, namely: Based on the analysis and strategy that will be used, several priority problems can be determined that can be handled immediately by considering the elements of strength, weakness, opportunity, and the threat that tend to be at the quadratic IV coordinate point, namely Aggressive. This means that there is strength to support Thomas R Dye's theory; it must be encouraged by the government in the form of a commitment to progress and activities to organize the Mutual Cooperation Village program.